CRYPTOCURRENCY DALAM KAJIAN FIQIH MUAMALAH - Siti Ramadhani; Rahmayani; Muhammad Radit Fazilah; Fatmah Taufik Hidayat (PT. Hasba Edukasi Mandiri, 2026)
The development of digital technology has given rise to cryptocurrencies, or crypto assets, as a new form of asset in the modern financial world. From the perspective of Islamic jurisprudence (fiqh muamalah), crypto continues to exist because it offers benefits, but it also carries elements of uncertainty, speculation, and a high risk of loss. Some scholars believe that crypto should not be used as a medium of exchange because it does not meet the requirements of a clear and stable currency. However, as an asset or commodity, crypto can be viewed more flexibly as long as it does not contain elements of usury, gharar, and maysir. Therefore, the assessment of crypto in Islamic jurisprudence (fiqh muamalah) requires considering the intended use, level of benefit, clarity of object, and compliance with Sharia principles. Therefore, crypto is viewed not only from a technological perspective but also from the perspective of fairness, benefit, and protection for transacting parties.